2008
DOI: 10.1038/cdd.2008.54
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of SHP2 leads to mesenchymal to epithelial transition in breast cancer cells

Abstract: The Src homology phosphotyrosyl phosphatase 2 (SHP2) is an essential transducer of mitogenic and cell survival signaling in the epidermal growth factor receptor (EGFR) signaling pathway. However, the role of SHP2 in aberrant EGFR and human EGFR2 (HER2) signaling and cancer, particularly in breast cancer, has not been investigated. Here, we report that SHP2 is required for mitogenic and cell survival signaling and for sustaining the transformation phenotypes of breast cancer cell lines that overexpress EGFR and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
89
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 38 publications
6
89
0
Order By: Relevance
“…Genetic and biochemical studies in recent years have suggested that SHP2 plays a broad role not only in cell proliferation [12], survival [13], and differentiation [14], but also in development [15,16] and tumorigenesis [17][18][19] of malignancies via Ras/Erk [20], PI3K/Akt [21] and other signaling pathways. In accordance to a recent study [18], our previous studies [22][23][24] have demonstrated that SHP2 plays a crucial role in breast oncogenesis. Recently, we have also found for the first time that SHP2 is widely expressed by lung cancer cells, and that the high expression of SHP2 may promote the invasion and metastasis of NSCLC through angiogenesis and the lymphatic system [25,26].…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Genetic and biochemical studies in recent years have suggested that SHP2 plays a broad role not only in cell proliferation [12], survival [13], and differentiation [14], but also in development [15,16] and tumorigenesis [17][18][19] of malignancies via Ras/Erk [20], PI3K/Akt [21] and other signaling pathways. In accordance to a recent study [18], our previous studies [22][23][24] have demonstrated that SHP2 plays a crucial role in breast oncogenesis. Recently, we have also found for the first time that SHP2 is widely expressed by lung cancer cells, and that the high expression of SHP2 may promote the invasion and metastasis of NSCLC through angiogenesis and the lymphatic system [25,26].…”
Section: Introductionsupporting
confidence: 63%
“…Shp2 was reported to be a modulator that prolongs the activation of Erk [18,20,22], which suggests its role in carcinogenesis and development of several kinds of malignancies. Furthermore, Lima et al [36] reported that insulininduced IRS-1/SHP2 complex was associated with insulin resistance and played a role in the control of AKT phosphorylation in an animal model.…”
Section: Shp2 Is Upstream Of Ras and Pi3k Pathways And Plays A Importmentioning
confidence: 99%
“…Inhibition of SHP2 suppressed EGF-induced activation of the Ras extracellular signalregulated kinase (ERK) and phosphatidylinositol 3-kinase (PI3K)-Akt signaling pathways in breast cancer cell lines, induced epithelial cell morphology, and led to reversion to a normal breast epithelial phenotype (40). Furthermore, E-cadherin was upregulated, and fibronectin and vimentin were downregulated (40). These data suggest that ERK also plays an important role in the process of MET (Fig.…”
Section: Mechanism Of Metmentioning
confidence: 67%
“…As noted above, the activity of Akt in breast carcinoma was shown to be repressed during MET, suggesting that repression of Akt activity may be related to MET (40). It was also shown that MET induced by BMP2 in mesenchymal colon carcinoma cells (CT26; ref.…”
Section: Mechanism Of Metmentioning
confidence: 84%
See 1 more Smart Citation